2002
DOI: 10.1016/s0006-3495(02)75604-x
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence for Phototropin-Related Blue-Light Receptors in Prokaryotes

Abstract: A prokaryotic protein, YtvA from Bacillus subtilis, was found to possess a light, oxygen, voltage (LOV) domain sharing high homology with the photoactive, flavin mononucleotide (FMN)-binding LOV domains of phototropins (phot), blue-light photoreceptors for phototropism in higher plants. Computer-based three-dimensional modeling suggests that YtvA-LOV binds FMN in a similar pocket as phot-LOVs. Recombinant YtvA indeed exhibits the same spectroscopical features and blue-light-induced photochemistry as phot-LOVs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
353
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(375 citation statements)
references
References 29 publications
22
353
0
Order By: Relevance
“…1B). These results are consistent with the result of Losi et al (2002), and indicating that the LOV domain of YtvA senses blue light.…”
Section: The Cys62 Residue Of Ytva Is Essential For Sensing Blue Lightsupporting
confidence: 91%
“…1B). These results are consistent with the result of Losi et al (2002), and indicating that the LOV domain of YtvA senses blue light.…”
Section: The Cys62 Residue Of Ytva Is Essential For Sensing Blue Lightsupporting
confidence: 91%
“…There are several established examples of photoexcited flavoproteins that function as photoreceptors of blue light, 48 for example, YtvA from B. subtilis. 49 It could also be suggested that inactivation of TrxR results in an oxidized thiol redox environment that activates redox-sensitive transcription factors such as Spx. 50 In general, blue light at wavelengths of ≤470 nm has an antibacterial effect.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The FMN binding modules belong to the PAS (PER/ARNT/ SIM) domain superfamily (15,16) occurring in many regulatory proteins and have been designated as LOV 1 domains; the acronym is based on the involvement in the signaling of light, oxygen, or voltage levels (10,17). Very recently, the presence of a LOV domain with similarity to the photoactive LOV domains of the phototropin of higher plants has been identified in the non-photosynthetic soil bacterium Bacillus subtilis (18).…”
mentioning
confidence: 99%